Факторите на модернизација на системот на управата за јавни приходи во процесот на приближување кон ЕУ - Омери, Фарук (Економски факултет, УКИМ, Скопје, 2014)
The main objective of a PhD dissertation is, through scientific approach, to explain and understand the importance and necessity of system modernization: The Public Revenue Office of the Republic of Macedonia, according to occurring environment changes and ones yet to follow, particularly in the fiscal and financial sector, as well as the need for compatibility with similar institutions in EU Member States, which is important as aspirant on the path to EU integration. For this defined objective, a starting point is construction of a modern system for the Public Revenue Office and in particular, the adjustment of the same to EU standards. This will depend on the level of preparedness for facing new changes in the period of transition, which our country is still undergoing. Therefore, the subject of this dissertation is the need of permanent modernization and strengthening of the institutional capacity of the system: the Public Revenue Office, organizational and managerial changes within it, human resource development as well as technological modernization and the importance of IT which as a product should cause a transformation within the system: the Public Revenue Office in actual service for taxpayers, simultaneously compatible with similar institutions in EU Member States.
The Modernization factors of Public Revenue Office of Republic Macedonia in the Process of Integration in EU
Докторска дисертација одбранета во 2014 година на Економскиот факултет во Скопје, под менторство на проф. д–р Златка Поповска.
Keywords: technological development, globalization, tax system, integration processes, institutional capacity, system: the Public Revenue Office, structure placement and efficiency, reform changes, management structure, human resources, knowledge and skills, information technology, effects of new technologies.